Hindu Priest, San Fernando, Trinidad - (:unkn) unknown (My University, 2008)
Photo of an elderly East Indian holy man in traditional wear.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; East Indians--Trinidad and Tobago; Men--Trinidad and Tobago; Ethnic costume--India